Studi Performa PC Cluster - Arni S. Sakul; Arthur M. Rumagit; Brave A. Sugiarso (Jurnal Teknik Elektro dan Komputer, 2014)
Abstract The development of computer and network technologies led to the idea to combine multiple computers in a network, where the computer is able to cooperate into processing a problem. PC cluster is an amalgamation of several computers to process a job of processing, which way of submit the task / job to every computer and produces very high speed result. This study used PC clusters for cracking passwords. Password Cracking John The Ripper is a process of opening a password in this case Windows XP SP 2.  The network topology used is a star topology and uses the internet protocol (IP) class C (192.168.1.0/24). The number of nodes consists of  three nodes, that are two slave nodes, one master node and one computer for sampling password. By doing so, the result can be seen the difference time between cracking passwords using  single computer and  PC cluster.After testing, it was found that the cracking using PC cluster is faster than  single computer. Keywords:  BackTrack 4R 2, John the ripper mpi8, message passing interface (MPICH2), PC cluster.  Abstrak Perkembangan teknologi komputer dan jaringan memunculkan ide untuk menggabungkan beberapa komputer dalam suatu jaringan dan dapat bekerjasama dalam memproses suatu program atau berkas yang berat. Aplikasi dari hal  ini adalah PC (Personal Computer) cluster. PC Cluster merupakan penggabungan beberapa komputer untuk memproses suatu pekerjaan, pemrosesan dengan cara membagi-bagikan task/job ke tiap computer sehingga menghasilkan kecepatan yang sangat tinggi. Penelitian ini memanfaat PC cluster untuk melakukan cracking password. Cracking Password John The Ripper adalah suatu proses pembuka password dalam hal ini windows XP SP 2. Topologi jaringan yang digunakan adalah topologi star dan menggunakan internet protocol(IP) kelas C (192.168.1.0/24). Banyaknya nodes berjumlah tiga node, yaitu dua slave node, satu master node serta satu komputer untuk pengambilan sample password. Setelah dilakukan pengujian maka didapatkan bahwa cracking menggunakan PC cluster lebih cepat dibandingkan dengan single computer. Kata Kunci : BackTrack 4 R2, John the ripper mpi8, message passing interface (MPICH2), PC cluster.